Employability of the Bachelor of Science in Business Administration Graduates (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
As businesses continue to evolve and adapt to the ever-changing demands of the global marketplace, the need for highly skilled and adaptable professionals has never been greater. In this dynamic landscape, the Bachelor of Science in Business Administration (BSBA) degree has emerged as a cornerstone of business education, equipping graduates with the foundational knowledge and transferable skills necessary to thrive in various industries and roles. This study delves into the employability of BSBA graduates, examining their employment rates, job placement trends, and the skills and competencies that contribute to their success in the workforce. By analyzing these key factors, the study aims to provide valuable insights into the effectiveness of BSBA programs in preparing graduates for the demands of the modern business world.This study used the descriptive research method to describe the employability of the UCC BSBA graduates from SY 2017 to 2022, with actual respondents of 61.68% from the entire 107 graduates. An adopted questionnaire was used to gather the needed data, which was done per the College's research protocols and guidelines. Descriptive statistics was used to analyze the data gathered.The findings of the study revealed that:• As to the employment profile, overall, it is positive, having the majority of them (85.9%) employed. They can find employment within a short period after graduation (89.1% found employment within one month to 1 year), with permanent employment at 62.5% in private organizations (40.6%) and government organizations (34.4%). The most common platform for getting employment is through friends or relatives (59.4%).• Secondly, the most influential factors in graduates’ employment are the quality of the college and the relevance of the program training. The other factors, such as the college’s accreditation status, the reputation of the faculty, and the college’s facilities, are also important but not as influential as the first two factors.• the most influential factors in getting immediate employment are good academic standing, excellent oral and written communication in English and Filipino, and personality factors (i.e., confidence and determination). The other factors, such as being a LET Passer/Civil Service Career Eligibility Passer, having a graduate with another course, and having political or company connections, are also influential but not as influential as the first three factors.• Conversely, the most challenging factors in the respondents’ employment included ‘too many applicants,’ ‘poor communication skills,’ and ‘mismatch of college training to industry skills.’ The other factors, such as no/inadequate experience, few job vacancies/opportunities, no advanced/further studies, limited ICT skills/proficiency, no political/company connections, not pressured to find one, passive personality, and salary is not competitive, are also influential but not as influential as the first three factors.• Meanwhile, the most influencing plus factors in getting employed include a. courage of the respondents to take chances and compete with other applicants for the job, b. attended seminars, and c. sought the endorsement of powerful individuals with connections to the company applied for. The other factors, such as taking other jobs not related to profession/education, enrolling in advanced studies, enrolling in speech/communication training, taking skills/trade training for in-demand jobs, enrolling in ICT classes, and taking up personality development courses, are also influential but not as influential as the first three factors.From the findings of the study, the researchers shed light on the following implications for the business education program of the Union Christian College, which can be relevant to the other degree programs of the institution and to other institutions within the region, national, and even global communities:• The college should continue its effective curriculum and teaching methodologies that contribute to graduates' success in the workforce, improving its reputation and attracting prospective students.• Establish and maintain strong ties with employers, leading to valuable partnerships, internship opportunities, and direct input on the relevance of the curriculum to industry needs. Collaboration with employers ensures that the college stays abreast of industry trends, helping it tailor its programs to meet the evolving needs of the workforce.• Ongoing investments in quality assurance and faculty recruitment/retention are vital for sustaining and enhancing the college’s standing, ensuring it remains an attractive choice for students and employers.• Regular assessments and curriculum updates in collaboration with industry partners will ensure that graduates are equipped with skills that align with current workforce demands.• Maintaining academic rigor is essential, as it contributes not only to graduates’ academic standing but also to their overall preparedness for the challenges of the professional world.• Effective communication skills are crucial in the workplace. Offering specialized courses and workshops will enhance graduates’ ability to articulate their ideas and contribute to their success in various professional roles.In closing, the study delved into the employability of the business education students at the college in a certain period. The participants were quite small, affecting the generalizability of the findings. As such, replication of the study for a wider scope and with a greater number of respondents can further establish the validity and reliability of this study.
Keywords: Program Success; Graduates'Employability; College Reputation; Quality Assurance; Relevant Curriculum